2022
DOI: 10.3390/rs14194904
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Hydrological Resources in Surface Water Change by Satellite Altimetry

Abstract: Satellite altimetry technology has unparalleled advantages in the monitoring of hydrological resources. After decades of development, satellite altimetry technology has achieved a perfect integration from the geometric research of geodesy to the natural resource monitoring research. Satellite altimetry technology has shown great potential, whether solid or liquid. In general, this paper systematically reviews the development of satellite altimetry technology, especially in terms of data availability and progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 175 publications
(180 reference statements)
0
1
0
Order By: Relevance
“…Remote sensing data have been widely used in the monitoring and research of alpine lakes. The long time series of lake area information can be obtained from remote sensing images easily and quickly, and altimetry satellites provide the surface elevation information of lakes within the period of the satellite operation; therefore, these sources can provide important data support for the study of the water balance of lakes [10][11][12][13][14]. Wang et al used multiple source altimetry satellite data and Landsat series satellite imagery data to monitor the variation in water storage in Qinghai Lake in recent years, and found that the increase in water storage in Qinghai Lake over the past 8 years was significantly greater than the increase observed 10 years ago [15].…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing data have been widely used in the monitoring and research of alpine lakes. The long time series of lake area information can be obtained from remote sensing images easily and quickly, and altimetry satellites provide the surface elevation information of lakes within the period of the satellite operation; therefore, these sources can provide important data support for the study of the water balance of lakes [10][11][12][13][14]. Wang et al used multiple source altimetry satellite data and Landsat series satellite imagery data to monitor the variation in water storage in Qinghai Lake in recent years, and found that the increase in water storage in Qinghai Lake over the past 8 years was significantly greater than the increase observed 10 years ago [15].…”
Section: Introductionmentioning
confidence: 99%